2022
DOI: 10.3390/cancers14143437
|View full text |Cite
|
Sign up to set email alerts
|

A Novel ALDH1A1 Inhibitor Blocks Platinum-Induced Senescence and Stemness in Ovarian Cancer

Abstract: Ovarian cancer is a deadly disease attributed to late-stage detection as well as recurrence and the development of chemoresistance. Ovarian cancer stem cells (OCSCs) are hypothesized to be largely responsible for the emergence of chemoresistant tumors. Although chemotherapy may initially succeed at decreasing the size and number of tumors, it leaves behind residual malignant OCSCs. In this study, we demonstrate that aldehyde dehydrogenase 1A1 (ALDH1A1) is essential for the survival of OCSCs. We identified a fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Considering the potential association between platinum resistance with the tumor heterogeneity and clinical outcomes of BLCA, we developed the PRR scoring system based on seven key genes associated with platinum resistance. More specifically, ALDH1A1, DSG1, LDLR, NRP2, and P4HB were considered risk factors, while IFNG and IL17A were favorable genes for platinum resistance, which is consistent with the current studies ( 20 23 ). As expected, cluster A exhibited the highest PRR score, while cluster C had the lowest PRR score, and cluster B showed a moderate PRR score.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the potential association between platinum resistance with the tumor heterogeneity and clinical outcomes of BLCA, we developed the PRR scoring system based on seven key genes associated with platinum resistance. More specifically, ALDH1A1, DSG1, LDLR, NRP2, and P4HB were considered risk factors, while IFNG and IL17A were favorable genes for platinum resistance, which is consistent with the current studies ( 20 23 ). As expected, cluster A exhibited the highest PRR score, while cluster C had the lowest PRR score, and cluster B showed a moderate PRR score.…”
Section: Discussionsupporting
confidence: 89%
“…ALDH1A1 , a member of the ALDH family, is highly expressed by stem cells in cancer ( 55 ). Da et al ( 56 ) recently found that ALDH1A1 was associated with cardiac development and protection after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Key antioxidant molecules, including glutathione peroxidase 4 (GPX4), nuclear factor erythroid 2-related factor 2 (NRF2) ( 166 ), and ALDH1 ( 167 ), are upregulated in cancer stem cells and in resistant cells and tumors ( 151 ). Notably, small molecules that block ALDH activity ( 168 , 169 ) resensitize OC cells to chemotherapy by reducing the antioxidant defense and suppressing Pt-induced senescence and stemness features. Likewise, small-molecule inhibitors targeting GPX4 eliminated Pt-resistant cells via ferroptosis, an iron and lipid peroxidation-dependent form of cell death ( 151 ).…”
Section: Advances In Therapymentioning
confidence: 99%